2012
DOI: 10.2224/sbp.2012.40.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Extra Care Housing Residents Aged Fifty-Five and Over with Home-Based Technology

Abstract: Technological interventions could help older people live independently. In this study with 160 people aged 55 and over who were living in extra care housing in England we aimed to explore awareness of, access to, attitudes towards availability, and use of home-based technological (HBT) devices, and factors that influence the use of devices. A quantitatively designed and structured questionnaire was developed for this study. The majority of new HBT devices were not available in living units or schemes. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Also in the list of potential barriers to the adoption of ATs are uncertainty about the appropriate time for ATs intervention, lack of information and support from formal health and social care services about how to access AT, where to source it and when and how it can be used [47,56] respectively. Peek, Luijkx [57] found six major evidences that seem to influence the level of technology use in the context of aging in place: challenges in the domain of independent living; behavioral options; personal thoughts on technology use; influence of the social network; influence of organizations, and the role of the physical environment.…”
Section: Source: Developed For This Studymentioning
confidence: 99%
“…Also in the list of potential barriers to the adoption of ATs are uncertainty about the appropriate time for ATs intervention, lack of information and support from formal health and social care services about how to access AT, where to source it and when and how it can be used [47,56] respectively. Peek, Luijkx [57] found six major evidences that seem to influence the level of technology use in the context of aging in place: challenges in the domain of independent living; behavioral options; personal thoughts on technology use; influence of the social network; influence of organizations, and the role of the physical environment.…”
Section: Source: Developed For This Studymentioning
confidence: 99%
“…Recent research related to technology adoption among older adults has indicated that older adults are increasingly familiar with digital technologies [ 10 - 12 ] and are interested in using technology to manage their health, such as measuring heart rate, keeping an activity diary, and monitoring stressful situations [ 13 , 14 ]. However, older adults’ experiences with technology can vary greatly, and many factors can influence whether an older adult successfully uses technologies for health self-management.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research related to technology adoption among older adults has indicated that older adults are increasingly familiar with digital technologies [10][11][12] and are interested in using technology to manage their health, such as measuring heart rate, keeping an activity diary, and monitoring stressful situations [13,14]. However, older adults' experiences with technology can vary greatly, and many factors can influence whether an older adult successfully uses technologies for health self-management.…”
Section: Introductionmentioning
confidence: 99%